Al-AsfÄr al-Arbaâ€˜at sebagai Basis Metafisika MullÄ ShadrÄ - Effendi, Rahmat (Tribakti: Jurnal Pemikiran Keislaman, 2021)
ShadrÄ, who is known as the leader of Islamic philosophy, succeeded in synthesizing various views of the previous schools of thought. His philosophy is al-Hikmat al-Muta'Äliyat which means transcendent wisdom as a transmission of wisdom that is directly present in a person through inner cultivation and spiritual purity. The synthesis is listed in the magnum opus, namely al-AsfÄr al-Arba'at. What and how ShadrÄ builds philosophical ideas on top of mystical and rational approaches is a speciality in ShadrÄ's philosophy. The existence of a relationship between each travel hierarchy and its philosophy is the focus of discussion in this study. This article is a literature study based on descriptive-analytical and holistic methods. The aim is to reveal how the hierarchy of SadrÄ's spiritual journey relates to the building of his philosophy. Then look at the concept holistically that there is a connection between mystical experiences that contribute to building a holistic and diverse philosophical system.